2014
DOI: 10.1371/journal.pone.0100935
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Genes and Emotional Reactivity to Daily Life Events: A Multi-Step Gene-Environment Interaction Study

Abstract: Recent human and animal studies suggest that epigenetic mechanisms mediate the impact of environment on development of mental disorders. Therefore, we hypothesized that polymorphisms in epigenetic-regulatory genes impact stress-induced emotional changes. A multi-step, multi-sample gene-environment interaction analysis was conducted to test whether 31 single nucleotide polymorphisms (SNPs) in epigenetic-regulatory genes, i.e. three DNA methyltransferase genes DNMT1, DNMT3A, DNMT3B, and methylenetetrahydrofolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…More specifically, MCI subjects carrying the TT genotype at rs11887120 in DNMT3A in both cohorts showed greater cognitive decline over time than CC carriers. In addition, we observed statistically significant associations between SNP rs1265764 in DNMT3A and change in cognitive decline over time in both cohorts, albeit that the direction of effect was opposite to each other in the two samples, which may be related to 'flip-flop' patterns of genetic association [12].…”
Section: Resultsmentioning
confidence: 66%
“…More specifically, MCI subjects carrying the TT genotype at rs11887120 in DNMT3A in both cohorts showed greater cognitive decline over time than CC carriers. In addition, we observed statistically significant associations between SNP rs1265764 in DNMT3A and change in cognitive decline over time in both cohorts, albeit that the direction of effect was opposite to each other in the two samples, which may be related to 'flip-flop' patterns of genetic association [12].…”
Section: Resultsmentioning
confidence: 66%
“…Epigenetic states are also modified by the emotional health of an individual as studies were done with psychosis, psychotic disorders, and severe depression [101]. Anti-androgenic compound ‘vinclozolin’, an anti-fungal agent used in vineyards or chemical methoxychlor, an oestrogenic compound used as a pesticide, can cause reproductive abnormalities in laboratory animals.…”
Section: Epigenetic Mechanisms Of Infection and Inflammationmentioning
confidence: 99%
“…Epigenetics seeks to elucidate these interactions affecting gene expression, such as the influence of child maltreatment on those with genetic vulnerability (Yang et al, ). Recent research has shown how daily events can have an impact on the epigenetic regulatory genes and that emotional responses may be moderated by the genetic variations in the genes that control epigenetic processes (Pishva et al, ). Studies also indicate that epigenetic mechanisms are especially vulnerable to disruption during critical phases of development, including gestation, infancy, puberty, and old age (Feinberg, ; Kerverne, ).…”
Section: Epigenetics and Psychiatrymentioning
confidence: 99%